Responsivitas Bidang Pemadam Kebakaran (PMK) Dalam Menangani Bencana Kebakaran di Kabupaten Tolitol - Ayu Lestari (Jurnal Multidisiplin Madani, 2022)
The main focus of the Fire Department. If viewed from the substance of the importance of an agency in terms of tackling fires, it is very necessary to have an excellent service quality to provide fire handling services which are increasingly prevalent at the end of this decade. Responsiveness is the ability to recognize community needs, develop service agendas and priorities, and develop service programs according to community needs and aspirations. The purpose of this study was to determine the responsiveness of services in the Tolitoli District Fire Department in dealing with fire disasters in Sidoarjo Village. This research was conducted by purposive sampling technique, using 12 informants. The method used is a descriptive method with a qualitative approach. Based on the results of research on the Responsiveness of the Tolitoli District Fire Department. Of the 6 indicators, there are 4 that have been implemented.